2020
DOI: 10.3399/bjgpopen20x101078
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ perspectives on estimating and communicating prognosis in palliative care: a cross-sectional survey

Abstract: BackgroundAdvance care planning (ACP) can help to enhance the care of patients with limited life expectancy. Despite physicians’ key role in ACP, the ways in which physicians estimate and communicate prognosis can be improved.AimTo determine how physicians in different care settings self-assess their performance in estimating and communicating prognosis to patients in palliative care, and how they perceive their communication with other physicians about patients’ poor prognosis.Design & settingA survey stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Although literature suggests that many patients value honesty and timely delivery of such discussions (42,43), GPs' and patients' ambivalence impedes such (42,44). Palliative care training and the use of prognostic tools are proposed to promote initiation of such discussions (45,46), however, this review found such tools to be infrequently used suggesting that further work is needed to enhance their clinical utility as conversation triggers.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Although literature suggests that many patients value honesty and timely delivery of such discussions (42,43), GPs' and patients' ambivalence impedes such (42,44). Palliative care training and the use of prognostic tools are proposed to promote initiation of such discussions (45,46), however, this review found such tools to be infrequently used suggesting that further work is needed to enhance their clinical utility as conversation triggers.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…However, it is complex to distinguished appropriate versus inappropriate care at the end of life: interventions that can be considered 'aggressive care' for some patients can be used to manage and alleviate symptoms and suffering in others [1][2][3]. Prognostication of patients with advanced cancer is difficult on an individual basis and it is complex to predict which patients would benefit from a medical intervention [34]. Moreover, this study only collected data about medical interventions as provided in the hospital; information on interventions outside the hospital is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also found deficits in the exchange of information between care settings regarding patients with palliative care needs (den Herder‐van der Eerden et al, 2017; Flierman et al, 2020; Seamark et al, 2014). In a survey about estimating and communicating about patients' poor prognosis, it was found that 83% of 205 hospital physicians indicated that they usually inform general practitioners about agreements regarding treatment and care for patients with a limited life expectancy who are discharged from hospital, whereas only 29% of 259 general practitioners indicated that they are usually adequately informed about such patients (Engel et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Information about patients' limited life expectancy was more often found in the medical record and hospital discharge letter for patients who died within 3 months after hospital admission than for patients who died after more than 3 months. Other studies also found that physicians tend to find it difficult to estimate or discuss a limited life expectancy of more than 3 months (Engel et al, 2020; White et al, 2016). Other reasons for not documenting such information could be that the hospital physician feels that the patient cannot cope with such information (Meeussen et al, 2011; Simon et al, 2015), uncertainty of prognostication and about these conversations (Bernacki et al, 2014; Flierman et al, 2020; Owusuaa et al, 2021) or that the hospital physician does not perceive this to be his or her responsibility (Flierman et al, 2020; Greysen et al, 2012; Heyland et al, 2013).…”
Section: Discussionmentioning
confidence: 99%